1984
DOI: 10.2307/3576050
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Irradiation of Late Mouse Embryos (15-19 Days) in Utero

Abstract: Pregnant female C57B1/6 mice were irradiated with a single whole-body dose of 0.5 Gy neutrons. The F1 hybrid embryos were exposed to the neutrons in utero on Day 17 +/- 2 of gestation. 178/439 (40.6%) of the irradiated fetuses and 26/217 (12%) of the control mice died within 2 weeks after birth. In both irradiated and control mice, most deaths (95 and 77%, respectively) occurred within 3 days of birth: most animals in both groups died on Day 2. There was no significant difference in the number of living young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Other than the brain changes, while several organs and tissues weights were decreased, atrophic changes were only seen in the genital organs of the high dose groups of neutrons, and also of gamma-rays. A decrease of testis weight was also reported by Vogel et al 12 in BDF1 mice prenatally irradiated with neutrons. Though the mechanisms of testicular atrophy observed in this study was obscure at the present, examination on the early changes in the testis, such as cell death of spermatogonia, may provide us some information about its mechanism.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…Other than the brain changes, while several organs and tissues weights were decreased, atrophic changes were only seen in the genital organs of the high dose groups of neutrons, and also of gamma-rays. A decrease of testis weight was also reported by Vogel et al 12 in BDF1 mice prenatally irradiated with neutrons. Though the mechanisms of testicular atrophy observed in this study was obscure at the present, examination on the early changes in the testis, such as cell death of spermatogonia, may provide us some information about its mechanism.…”
supporting
confidence: 51%
“…Neuro-hormonal regulation such as growth hormones, or cell proliferation regulation and/or apoptosis in those organs and tissues may be involved in their mechanisms. On the other hand, Vogel et al 12 reported that decreases of the body weight and the brain weight were much more significant in the mice irradiated at E17 than in the mice irradiated at E15, so that the pathological examination of early cell death and cell growth inhibition in the organs and tissues, in relation to the developmental phase, may provide us good information about the mechanisms and characteristics of the underdevelopment of mice prenatally exposed to neutrons.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The greatest sensitivity to radiation was found in early stages of prenatal development, mainly between weeks 8 and 15 of gestation (Dobbing and Sands, 1973;Antal et al, 1984;Vogel and Antal, 1984;Kameyama and Hoshino, 1Y86).…”
Section: Introductionmentioning
confidence: 99%